A Novel Moist Carbon Dioxide Generation Enhanced Oil Recovery Technology - Panahov, Geylani M.; Abbasov, Eldar M.; Bakhtiyarov†, Sayavur I.; Agayeva, Gulshan R. (Discontinuity, Nonlinearity, and Complexity, 2026)
A new technological technique based on the “moist” carbon dioxide generation in the wellbore zone of the oil formations or at the wellhead is proposed. In this new technology a carbon dioxide is generated as a result of the chemical reaction between an aqueous acid solution and a natural calcium carbonate rock (limestone) as a “gas yielding” component. The mechanism of the process allows controlling a generation rate and a volume of the gas, the thermobaric conditions of the oil formation, mineral and acidity levels of water and a phase state of carbon dioxide. An industrial application of this technology in a large scale has a significant ecological importance as this technology utilizes the wastes of processing plants of the natural minerals, which is consid- ered as a major source of the pollution of atmosphere by greenhouse gas emissions.